SEMINAR ANTI-BULLYING UNTUK MENCEGAH SUPERIORITY COMPLEX BAGI SANTRI ASRAMA TACHFIZHIL QUR’AN AL-IKHSAN BEJI KEDUNGBANTENG - Akhmad Sulaiman; Ramdhan Yurianto (Migunani Nusantara: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to strengthen Qur’anic interpretive literacy and ethical awareness among tahfidz students in preventing bullying behavior and superiority complex tendencies in Islamic boarding school settings. The program was conducted at Asrama Tachfizhil Qur’an PP al-Ikhsan, Beji, Kedungbanteng, involving tahfidz students at junior and senior secondary school levels. Initial observations and interviews indicated that bullying occurred in both verbal and physical forms. Verbal bullying appeared more frequently through mockery, negative labeling, and degrading jokes. The method consisted of preparation through observation and interviews, the implementation of an anti-bullying seminar, and evaluationThe seminar was entitled “Becoming Righteous Santri without Bullying in Preventing Superiority Complex in Pesantren.” The evaluation results showed an increase in students’ understanding. The average pre-test score was 56.25 and increased to 86.75 in the post-test, with an improvement of 30.50 points. This improvement indicates that the anti-bullying seminar based on Qur’anic interpretive literacy helped students understand the forms of bullying, Qur’anic prohibitions against degrading others, the dangers of superiority complex, and the importance of building a safe, empathetic, and violence-free pesantren culture.